Issues of Strengthening Civic Competence Through The Modernization of The “History of Uzbekistan” Course In Higher Education - O’g’li, Teshayev (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2025)
With an emphasis on efficiently structuring this process through the course “History of Uzbekistan”, the article emphasises the importance of fostering students’ civic engagement and social skills in the twenty-first century. It highlights the value of incorporating cutting-edge methods and pedagogical-psychological concepts – which are founded on sophisticated international educational practices – into instructional activities. Through education grounded in historical values, patriotism, and humanism, special attention is paid to fostering young people’s sense of personal and social responsibility as well as assisting them in becoming active citizens. The study examines the benefits of teaching “History of Uzbekistan” through project-based learning, creative exercises, self-directed thinking, and contemporary technology. An effective strategy for developing students’ civic competence is a pedagogical model with a scientific foundation